Answer:
Explanation:
A fucntion is basically a machine that follows the instructions it's given and based on those instructions it gives you an answer. So in the function
f(x)=-x+7, our total output (answer) is going to be whatever our "x" is and adding that to 7.
So lets start with -2, plug in -2 for the x variable
f(x)=-(-2)+7, when we solve this we get f(x)=2+7 (negative*negative=positive)
so our final function would be f(x)=9
We can solve the other functions by plugging in the x variable in the same way:
f(x)=-(-1)+7 this simplifies to f(x)=1+7, so f(x) equals 8
f(x)=-(0)+7 this simplifies to f(x)=0+7, so f(x)=7
f(x)=-(1)+7 this simplifies to f(x)=-1+7, so f(x)=6
f(x)=-(2)+7 this simplifies to f(x)=-2+7, so f(x)=5